2022
DOI: 10.3390/children9101466
|View full text |Cite
|
Sign up to set email alerts
|

Relationship Analogy between Sleep Bruxism and Temporomandibular Disorders in Children: A Narrative Review

Abstract: Sleep bruxism (SB) is a condition characterized by repetitive clenching or grinding teeth and/or by bracing or thrusting of the mandible during sleep. Although SB is not considered a disorder in children, SB can be a potential physical and psychological hazard or consequence, and this study examines whether SB is a risk factor for TMD as it is in adults. A narrative review on the topic of inferring the relationship between sleep bruxism and TMD in children was performed based on a search in the PubMed and Goog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 71 publications
(70 reference statements)
0
4
0
1
Order By: Relevance
“…The patients enrolled in the study suffered from temporomandibular disorders, not bruxism itself [33]. The manifestation of clenching in patients with temporomandibular disorders (TMD) can, however, be a reflection of bruxism [38]. Interleukin 6 (IL-6) and interleukin 8 (IL-8) levels increased in response to tooth clenching in both groups, while interleukin 7 (IL-7), interleukin 13 (IL-13) and tumor necrosis factor (TNF) rose only in patients with TMD-related myalgia.…”
Section: Search Results and A Synthesis Of Findings From Studies Incl...mentioning
confidence: 99%
“…The patients enrolled in the study suffered from temporomandibular disorders, not bruxism itself [33]. The manifestation of clenching in patients with temporomandibular disorders (TMD) can, however, be a reflection of bruxism [38]. Interleukin 6 (IL-6) and interleukin 8 (IL-8) levels increased in response to tooth clenching in both groups, while interleukin 7 (IL-7), interleukin 13 (IL-13) and tumor necrosis factor (TNF) rose only in patients with TMD-related myalgia.…”
Section: Search Results and A Synthesis Of Findings From Studies Incl...mentioning
confidence: 99%
“…Previous studies suggested a relationship between SB and TMD in children. SB can cause tooth wear, masticatory muscle pain, TMD pain, limited mouth opening, ear pain, and headaches [ 30 ]. Balasubramaniam et al [ 55 ] summarized the negative consequences possibly associated with SB, such as occlusal and incisal wear, tooth fracture, TMJ discomfort or pain, and even symptoms such as a reduction in salivary flow and/or xerostomia.…”
Section: Discussionmentioning
confidence: 99%
“…The SB grading systems, as suggested by the international consensus group, refer to a positive self-report of an adult subject or report of his/her sleeping partner regarding bruxing activity during sleep. Regretfully, young children’s self-report concerning SB is not reliable and diagnosis of SB in children is mostly based on reports of family members that describe the characteristic sounds of teeth grinding during sleep [ 30 ]. The use of a single question posed to parents/caregivers regarding the possible presence of SB via the existence of dental tightening or audible noises related to teeth grinding is an accepted way to determine SB in children [ 31 ].…”
Section: Methodsmentioning
confidence: 99%
“…Occlusal trauma and prolonged abnormal biting pressures will lead to crown or root fractures, accelerate periodontal breakdown, such as gingival atrophy, alveolar bone absorption, resulting in tooth mobility and displacement [16][17][18]. Severe dental attrition can lead to orofacial dysfunction, such as decreased vertical distance, temporomandibular joint disorders, disc perforation, orofacial muscular pain, and even restricted mouth opening [19][20][21][22].Therefore, for patients with bruxism, we need to take some measures to protect oral and maxillofacial system .…”
Section: Introductionmentioning
confidence: 99%